Liver Cirrhosis of the Viral Etiology in Children - F. I. Inoyatova; G Z. Inogamova (LLC "Diagnostics and Vaccines", 2018)
The structure of liver cirrhosis (LC) in children of Uzbekistan was studied. 135 children with viral etiology of liver cirrhosis at the age of 7-15 years of life were examined. It was established that in the structure of viral liver cirrhosis in children, mixed etiology prevails (77.1%) with a predominance of HDV infection (B + C + D - 35.6% and B + D - 23.7%). Mixed infection is considered as a predictor of disease progression, especially in cases of overlap of HDV infection, which was also expressed by the frequent identification of the decompensated stage of the liver cirrhosis C-class of Child-Pugh and complications. Levels of N-terminal propeptides and C-terminal telopeptides of type I collagen in children with liver cirrhosis can serve as markers of compensation and progression of the disease.